Latitude, habitat and reproductive outcome shape breeding space use in common redshanks : First insights from GPS tracking across European landscapes - Allain, Jimmy; Monnet, Anne-Christine; Jiguet, Frédéric; Deschamps, Julie; Piha, Markus; Seimola, Tuomas; Procházka, Petr; Rey, Fanny; Rousseau, Pierre; Jomat, Loic; Lemke, Hilger; Obracay, Thorsten; et al. (Elsevier, 2026)
The degradation and loss of breeding habitats due to agricultural intensification is driving severe declines in European bird populations. Understanding how breeding phenology and habitat use vary across a species’ breeding distribution is essential for effective conservation. Here, we investigate how phenology and space use vary across latitude and habitat types of the common redshank (Tringa totanus) with breeding sites distributed across Europe, encompassing coastal, bog and agricultural landscapes. We used high-resolution GPS telemetry to track 85 adult redshanks throughout the breeding season. We quantified timing of reproductive stages, local movement behaviour, home-range size and habitat use during incubation and chick-rearing, and assessed how these parameters varied with latitude, habitat type and reproductive outcome. Spring arrival dates were strongly structured by latitude, whereas post-breeding departure was more closely linked to reproductive outcome. Later-arriving individuals exhibited flexible adjustment of breeding schedules across sites by shortening the pre-laying phase. Departure timing depended on reproductive outcome, with similar post-failure departure of both sexes but prolonged male residency following successful hatching, which is consistent with sex-specific parental roles. Space use varied markedly among sites and was strongly driven by dominant habitat type. In coastal systems, mudflats were heavily used throughout the breeding cycle, whereas bog-breeding redshanks increasingly used bog habitats during brooding, reflecting favourable conditions for chick development. Redshanks breeding in grassland make significant use of agricultural areas benefiting from conservation measures. Our results reveal behavioural flexibility in reproductive phenology and habitat use across the European breeding range of the redshank, allowing us to identify phases sensitive to disturbance in different populations. Agricultural habitats can be suitable, but birds seem to use mainly grasslands under protection measures, highlighting the importance of the implementation of AES (Agri-environment Schemes) and cooperation with farmers for the conservation of shorebirds.
Keywords: shorebirds; conservation; habitat use; agriculture; Tringa totanus; Annual cycle; waders